Pandemic-specific coping, anxiety, and depression across multiple waves of COVID-19 in elite athletes with disabilities - Urbański, Piotr K.; Tasiemski, Tomasz; Brewer, Britton W. (Frontiers in Psychology, 2023)
Abstract Objectives: Competitive athletes have faced many of the same mental health challenges experienced by the general population during the COVID-19 pandemic. The purpose of the current study was to examine the extent to which pandemic-specific coping predicted anxiety and depression over and above general coping styles in elite athletes with disabilities across multiple waves of the COVID-19 pandemic. Methods: Participants were 91 (60 men, 31 women) athletes in the Polish Paralympic Preparation Program before the Tokyo Summer Paralympic Games and Beijing Winter Paralympic Games. The Coping Inventory for Stressful Situations and an open-ended item asking participants to describe coping resources they had used to overcome stressful situations caused by the pandemic were administered in April 2021, and the Hospital Anxiety and Depression Scale was administered in April, July, and November of 2021. Results General coping styles were not significantly associated with pandemic-specific coping, anxiety, or depression in the July and November 2021 assessments. Pandemic-specific coping was related prospectively to both anxiety and depression across the July and November 2021 when controlling for age, gender, general coping styles, and April 2021 anxiety and depression. Conclusion The findings suggest that elite athletes with disabilities may cope with pandemic-related stress differently from how they cope with stress in general and that pandemic-specific coping may be relevant to mental health outcomes during the COVID-19 pandemic. This information may be useful in the development of interventions to assist elite athletes with disabilities cope with pandemics and other atypical stressors.